KAJIAN MAKNA NGGAHI DANA DAN MAKKA PADA BUDAYA PENYAMBUTAN TAMU-TAMU BESAR DI DOMPU - Lili Suryaningsih; Rusdiawan Rusdiawan; Nuriadi Nuriadi (Center of Language and Cultural Studies, 2018)
The purposes of this study are to describe the meaning of nggahi funds and makka, a tradition to welcome honored guests in Dompu and to identify meanings in the nggahi and makka in the recent social values. The tradition was derived from the indigenous local cultures that currently was retained as one of the folklore so that the researchers approached using the ethnographic study. Three informants were interviewed, tradition ceremony to welcome guests was observed records were analyzed, and introspection was conducted. Analyses were done based on the verbatim transcripts of the traditions. The study revealed that four symbols apply in the nggahi fund traditions and two in makka having connotative and denotative meaning. Guests are greatly appreciated and served in high honors. Values as the Islamic teaching denote are embedded in the social interations in the nggahi and makka.